Long-term effectiveness, safety, and liver stiffness dynamics of PBC treatment with obeticholic acid in real-world - Francesca Terracciani; Antonio De Vincentis; Daphne D’Amato; Laura Cristoferi; Alessio Gerussi; Pietro Invernizzi; Miki Scaravaglio; Ester Vanni; Daniela Campion; Anna Morgando; Vincenzo Valiani; Vincenzo Boccaccio; et al. (JHEP Reports, 2025)
Background & Aims: Several studies have assessed the short-term effectiveness and safety of obeticholic acid (OCA) in the real-world setting. We aimed to extend knowledge on the real-world effectiveness and safety of OCA treatment by expanding sample size and follow-up, and by exploring changes in liver stiffness measurement (LSM) over time. Methods: The RECAPITULATE project involves centres belonging to the “Italian PBC registry” and/or the “Club Epatologi Ospedalieri” PBC working group. Effectiveness was evaluated as biochemical response according to POISE and normal range (NR) criteria (normal alkaline phosphatase/alanine aminotransferase/bilirubin). Safety was assessed as the incidence of de novo/worsening pruritus and discontinuation rate/causes. Available LSMs were also captured. Results: We included 747 patients from 66 Italian centres: mean age 58 years; female/male 88%/14%; median follow-up 24 months [IQR 12-42]; 28% with cirrhosis, and 14% with autoimmune hepatitis (AIH)/PBC overlap syndrome. Probabilities of POISE and NR response increased from baseline to 57% and 20%, respectively, by the 42nd month. The probabilities of response were lower in patients with cirrhosis (p = 0.02 and p = 0.004 for POISE and NR), but not different between patients with AIH/PBC and pure PBC (p = 0.8). Overall, 130 patients (17%) discontinued treatment, mainly due to pruritus (36.9%), while 28.5% did so after developing hepatic events. The discontinuation rate was higher in patients with cirrhosis (p <0.001). LSM was available in 573 patients (∼77%), of whom 255 had multiple measurements. LSM variation over time differed based on the attainment of POISE biochemical response (expected mean annual variation -0.48 [-0.78, -0.19] in responders vs. +0.33 [-0.07, 0.73] in non-responders, respectively, p <0.001). Conclusions: Our findings confirm the effectiveness and safety profiles of OCA in the medium/long term and demonstrate that biochemical response is associated with the change in LSM over time. Impact and Implications: After the conditional approval of OCA for the treatment of PBC, the main confirmatory study failed to demonstrate OCA's ability to reduce liver-related events, leading the EMA to revoke the drug's marketing authorization. The ensuing scientific debate highlights an urgent need for further evidence from real-world practice. In the largest real-world series of patients treated with OCA to date, we confirm that the drug's effectiveness and safety profiles are maintained over a medium-to-long follow-up period. Valuable data for the management of the drug in relevant subgroups of patients, such as those with cirrhosis and autoimmune hepatitis/PBC overlap syndrome, are also provided. Our original results on liver stiffness measurement variation over time suggest a favourable impact of OCA on fibrosis progression, particularly in patients achieving a biochemical response to the drug. Overall, these data provide important insights for clinicians managing patients with PBC and contribute to the ongoing scientific debate about the effectiveness/safety profile of this drug.